Efisiensi Teknis Usaha Tani Bawang Merah di Provinsi Aceh - Sarini Sri Utari; Dwi Rachmina; Netti Tinaprilla (Institut Pertanian Bogor, 2023)
This study aimed to estimate the level of efficiency and socio-economic factors that predispose the technical efficiency of shallot farming in Aceh Province based on differences in growing seasons. The data analysis method was estimated using the Stochastic Frontier Cobb-Douglas production function with the maximum likelihood estimation (MLE) approach. The 2014 Horticultural Crops Household survey data from the Central Statistics Agency (BPS). The number of samples was 143 shallot farming units. The results showed that seed production, fertilizer, labor, and the harvested area positively and significantly affected shallot output. Shallot farming in this province has been efficient at around 85,09%. Based on the growing season, the value of efficiency in the dry season is 90,08%, which is more efficient than farming in the rainy season, which is 70,03%. However, the technical efficiency value of shallots in the dry season and rainy season can still be improved. In addition to seasonal variables, significant factors affecting the efficiency of shallots are participation in farmer groups and land type, while education and seed sources have no considerable effect. The government's role is to provide quality seeds and conduct cultivation during the dry season to increase the technical efficiency of shallot farming. Keywords: farmer group, season, stochastic frontier, technical efficiency